Discrete mathematics and its applications - "Rose, Kenneth" (McGraw-Hill Education: London, 1999)
This text is designed for sophomore/junior-level introductions to discrete mathematics taken by students preparing for future coursework in areas such as math, computer science, and engineering. Rosen has become a bestseller largely due to how effectively it addresses the main portion of the discrete market, which is typically characterized as the mid- to upper level in rigor. The strength of Rosen's approach has been the effective balance of theory with relevant applications, as well as the overall comprehensive nature of the topic coverage.
Keywords: Mathematics - Teacher resource